A promising view of kudzu plant, Pueraria montana var. lobata (willd.) sanjappa & pradeep: Flavonoid phytochemical compounds, taxonomic data, traditional uses and potential biological activities for future cosmetic application - Duangjai Tungmunnithum (2020)
© 2020 by the authors. Pueraria montana var. lobata is widely known as kudzu especially in Japan, China, Korea, and other Asian countries. This plant is an ingredient for traditional food and an herbal ingredient for traditional medicines, particular in Japan and China. There are a few reports on its cosmetic uses. Interestingly, many phytochemical compounds from this plant have been continuously reported, particularly flavonoid compounds, which are well-known as potential bioactive ingredients for cosmetics. This work aims to illustrate promising views of kudzu plant, focusing on the diversity of flavonoid phytochemical compounds, taxonomic data, traditional uses, and potential biological activities for future cosmetic applications, i.e., antioxidant, antiglycation, skin regeneration, and melanogenesis inhibitory activities.